Estudo de uma descida de água modular por meio de modelo físico reduzido e CFD - Felipe Angelo Neves Campera (2020)
Stepped chutes have long been used in works of different sizes of urban infrastructure, road drainage, spillways, and mine drainage. The literature presents several previous devices studies in a dissociated way, making investigative for dimensioning the simultaneous functioning (stepped chute and stilling basin). As an example of the application of stepped chutes in sequential falls, there are, in the mining environment, drainage for mine waste dumps. The stepped chutes are built on the slopes, approximately 10 meters in height, followed by the shoulders, varying from 3 to 8 meters in length. A key issue is the dissipation of energy on the shoulders, as excessive dissipation can result in elevated subcritical depths, an uneconomic fact since there will be a new stretch of acceleration in sequence (next slope). For the investigation of a system (module), formed by the stepped chute and the stilling basin of variable configuration, a reduced physical model, adaptable for various scenarios, in scale 1:10, was built. Through shooting techniques with high frame frequency, results were obtained for similar, water and energy levels. Three scenarios were worked on in this research: smooth chute, stepped chute and the system formed by stepped chute and stilling basin. In parallel, with the high development of numerical simulations applied to Computational Fluid Dynamics (CFD), a comparative analysis of numerical modeling was developed through the two methods most used by the available software: the Finite Element Method (MEF) and the Finite Volume Method (MVF), both applied to the reduced physical model for the first two scenarios. The software used for this work was Autodesk® CFD, representative of the programs that algebraically discretize as Navier-Stokes equations by MEF, OpenFOAM®, which solves the same problem by MVF, and also, in a complementary exploratory way, FLOW-3D®, full three-dimensional model, also operated through the MVF. Due to the limitations of computers in this study, the complete three-dimensional model was exploratory. The investigations were carried out by the other first two software in a simplified way. The results for the system (module) established three main equations for the structure dimension process. In addition, the MVF was reaffirmed as the best performance for the conditions simulated in this study. Among the three turbulence models most applied to these hydraulic structures, k-ԑ, SST-k-ω and RNG, the RNG model indicated the best representation of the aerated flow during the tests.